The ionomics of three-spined stickleback on North Uist: elemental investigation of an ecological chemical mosaic - Hill, Iain (2023)
How does the abiotic chemistry of the environment affect biotic evolution? Organisms require approximately 25 elements to construct themselves, and the occurrence of these varies spatiotemporally in the environment, yet we know little about the elemental composition of animals beyond that of the commonest elements (C, N, P, K). Ionomics is the emerging study of the elemental sum of an organism’s ion makeup (i.e. the ionome), which focuses on the potential importance, relevance, and accessibility of all important compositional elements. These have become increasingly accessible through Inductively Coupled Plasma Mass Spectroscopy. The chemical and pH variation across the island of North Uist in the Scottish Western Isles, combined with the three-spined stickleback populations that inhabit the various lochs provides a unique study system with which to better understand chemical consequences for evolution and inform on how rapid changes to water chemistry and pH could affect fish populations. Multi-element analysis of fish and environmental components was combined with a common garden experiment, reciprocal water rearing and a developmental approach of staining for bone ossification, to investigate population ionomic variation, genotype vs. phenotype, adaptation and the consequences of water chemistry. Results showed that fish ionomics were population specific and directly affected by both water chemistry and nutritional availability. Invertebrate populations of prey items did not exhibit the same trends in site specific ionomics, though taxa specific differences were found and fish stomach contents indicated potential selective feeding behaviours. Ionomics exhibits plasticity under common chemical conditions, but has a genetic component and fish are still readily identifiable to their population of origin on an elemental level. Water rearing chemistry directly impacted hatching rates and hatching mortality as well as fish ionomics, growth and development. These results demonstrate not only the application of ionomics and multi-element analysis to questions of ecology, evolution and development, but also how such approaches can be integrated with more well established techniques and extremely suitable study systems to gain a better understanding of how biotic and abiotic components of environments interact to influence fish development, adaptation and evolution.